Music, Computing, and Health: A Roadmap for the Current and Future Roles of Music Technology for Health Care and Well-Being - Agres, Kat R.; Schaefer, Rebecca S.; Volk, Anja; van Hooren, Susan; Holzapfel, Andre; Dalla Bella, Simone; Müller, Meinard; de Witte, Martina; Herremans, Dorien; Ramirez Melendez, Rafael; Neerincx, Mark; Ruiz, Sebastian; et al. (Music & Science, 2021)
The fields of music, health, and technology have seen significant interactions in recent years in developing music technology for health care and well-being. In an effort to strengthen the collaboration between the involved disciplines, the workshop “Music, Computing, and Health” was held to discuss best practices and state-of-the-art at the intersection of these areas with researchers from music psychology and neuroscience, music therapy, music information retrieval, music technology, medical technology (medtech), and robotics. Following the discussions at the workshop, this article provides an overview of the different methods of the involved disciplines and their potential contributions to developing music technology for health and well-being. Furthermore, the article summarizes the state of the art in music technology that can be applied in various health scenarios and provides a perspective on challenges and opportunities for developing music technology that (1) supports person-centered care and evidence-based treatments, and (2) contributes to developing standardized, large-scale research on music-based interventions in an interdisciplinary manner. The article provides a resource for those seeking to engage in interdisciplinary research using music-based computational methods to develop technology for health care, and aims to inspire future research directions by evaluating the state of the art with respect to the challenges facing each field.
CRIS-Team Scopus Importer:2021-10-29
Keywords: health care; interdisciplinarity; MedTech; music information retrieval (MIR); music neuroscience; Music psychology; music technology; music therapy; well-being